A self adaptive telemetry station for flash flood early warning systems - Autanan Wannachai (2018)
© 2017 IEEE. For flash flood mitigation, the water level at the upstream river should be measured in a near real time manner to promptly assess the flood risk. In this paper, the water level monitoring telemetry stations have been designed and invented to keep tracking of the river water level. However, there is no electric power supply and no wired communication in the upstream river region. The telemetry station should be designed to cope with these challenges. This paper proposed a self adaptive telemetry station, SATS, that can automatically adjust its operation mode to the environmental conditions. An automatic environmental condition learning and evaluation mechanism, Auto-ELE, is also proposed in this paper. The proposed mechanism adaptively adjusts the telemetry station operation against the water level changes. The simulation results show that the proposed mechanism yields to reduce the battery utilization and keep accuracy of the data measurement.